(untitled) (مجلة المنصور, 2022)
The wireless body area network (WBAN) has emerged as a new technology for ehealthcare that allows the data of a patient’s vital body parameters and movements to be collected by small wearable or implantable sensors and communicated using short-range wireless communication techniques. WBAN has shown great potential in improving healthcare quality, and thus has found a wide range of applications. However, the security and privacy protection of the data collected from a WBAN, either while stored inside the WBAN or during their transmission outside of the WBAN, is a major unsolved concern. Challenges are mainly coming from stringent resource constraints of WBAN devices. The aim of this work is to achieve secure and dependable distributed data storage in the WBAN. At the first part of the paper, we will survey the most recent research directions in the field.Significant recent papers are discussed and compared to each other to identify the advantages and disadvantages of each technique. Then, our proposed strategy will be devoted based on that survey. The proposal is mainly based on the techniques of erasure coding, secret sharing and an algebraic signature to simultaneously achieve data confidentiality, dependability, and dynamic integrity.